DIGITALISASI PEMASARAN SERTA PENDAMPINGAN MANAJEMEN USAHA PADA UMKM ANGKRINGAN KMS DI TUMPANG KABUPATEN MALANG - Iklila Amiroh; Dita Rahmi Rahayu; Agung Winarno; Agus Hermawan (Jurnal Pemantik, 2022)
The development of MSMEs is increasingly rapid, not spared from increasingly fierce competition. The emergence of MSME competition if it is not balanced with adequate management, it will be difficult to develop and will be worse off being beaten by its competitors. Therefore digital marketing through social media and online marketplace platforms is urgently needed at this time. However, many MSME actors ignore digital marketing due to a lack of knowledge about technology. This also happened to the "Angkringan KMS" MSMEs located in Tumpang District, Malang Regency, which had not utilized digital technology in their business. Apart from not doing digital marketing, these MSMEs are also not good at financial management, as evidenced by the absence of financial records. The purpose of this research is that partners can develop because of digital marketing so that they can increase sales, partners can prepare financial reports properly, have a menu list design and logos for social media to attract and make it easier for consumers to buy products. This service research method is to carry out initial identification, analysis or planning, implementation and assistance, and evaluation. The results obtained from this activity are partners who understand digital marketing, simple financial reports, and design menu lists and logos for social media